Maintaining the benefits following pulmonary rehabilitation: Achievable or not?. Issue 9 (19th March 2019) - Spencer, Lissa M.; McKeough, Zoe J.
ABSTRACT: Pulmonary rehabilitation (PR) improves exercise capacity, health‐related quality of life (HRQoL) and dyspnoea in patients with COPD and other lung conditions. Once PR is completed, the benefits gained begin to decline unless patients continue to exercise regularly. Due to limited evidence in other lung conditions, this review aims to examine the current evidence regarding maintenance exercise programmes for patients with COPD and to determine the types of programmes that are able to maintain the benefits gained from PR to 12 months and longer. A number of factors may affect the ability to maintain exercise capacity and HRQoL in the long term including: frequency of supervised maintenance exercise; strategies used to improve adherence to maintenance exercise; facilitators and barriers to long‐term exercise training; and initial PR programme itself. The current evidence for maintenance exercise programmes that included supervised maintenance exercise was weak, and for those programmes that included unsupervised maintenance exercise (with and without support) were difficult to interpret and in many instances were no better than usual care. New research using technology has provided some promising results for the future and surveys have revealed important features that may help in the development of maintenance programmes from a participant perspective such as ongoing therapist support. How to best maintain the benefits gained from PR remains unclear. Therefore, it is likely that no one model of maintenance is ideal for all patients with COPD and that individually adapted maintenance exercise programmes need to be considered.